Aktivitas Pseudomonas Pendar Fluor Dalam Mengendalikan Penyebab Penyakit Patik (Cercospora nicotianae) Pada Tembakau - Hardian Susilo Addy (Jurnal Pengendalian Hayati, 2008)
This study was conducted for tenth month in laboratory and greenhouse of Plant protectionDepartment of Agriculture Faculty Jember university. This research was coonducted by two step invitro including identification and screening in laboratory,and in vivo including induce systemicresistant and leaf interaction of antagonist against patogen. The result show that activities offluorescent pseudomonad in vitro against C. nicotianae was by production antibiotic, proteases andsiderophore. Antagonistic invitro was effective under 20-30OC temperatures. Influence of ironconcentration at 5, 50 and 100 μM was affect on antagonist by siderophore, more high concentrationless ability to suppress C. nicotianae growth. In greenhouse test, all isolate was shown ability tocontrol C. nicotianae by induce plant resistant and by antibiosis activities.